Basic emergency care course and longitudinal mentorship completed in a rural Neno District, Malawi: A feasibility, acceptability, and impact study. - Brown David Khongo; Kelly Schmiedeknecht; Moses Banda Aron; Prisca Nelisa Nyangulu; Wellington Mazengera; Enoch Ndarama; Andrea G Tenner; Kimberly Baltzell; Emilia Connolly (PLoS ONE, 2023)
Background Frontline providers mostly outside specific emergency areas deliver emergency care around the world, yet often they do not receive dedicated training in managing emergency conditions. When designed for low-resource settings, emergency care training has been shown to improve provider skills, facilitate efficient use of available resources, and reduce death and disability by ensuring timely access to life-saving care. Methods The WHO/ICRC Basic Emergency Care (BEC) Course with follow up longitudinal mentorship for 6 months was implemented in rural Neno District Malawi from September 2019-April 2020. We completed a mixed-methods analysis of the course and mentorship included mentor and participant surveys and feedback, mentorship quantification, and participant examination results. Simple descriptive statistics and boxplot visuals were used to describe participant demographics and mentorship quantification with a Wilcoxon signed-rank test to evaluate pre- and post-test scores. Qualitative feedback from participants and mentors were inductively analyzed using Dedoose. Results The median difference of BEC course examination percentage score between participants before the BEC course and immediately following the course was 18.0 (95% CI 14.0-22.0; p<0.001). Examination scores from the one-year post-test was lower but sustained above the pre-course test score with a median difference of 11.9 (95% CI 4.0-16.0; p<0.009). There were 174 mentorship activities with results suggesting that a higher number of mentorship touches and hours of mentor-mentee interactions may assist in sustained knowledge test scores. Reported strengths included course delivery approach leading to improved knowledge with mentorship enhancing skills, learning and improved confidence. Suggestions for improvement included more contextualized training and increased mentorship. Conclusion The BEC course and subsequent longitudinal mentorship were feasible and acceptable to participants and mentors in the Malawian low resource context. Follow-up longitudinal mentorship was feasible and acceptable and is likely important to cementing the course concepts for long-term retention of knowledge and skills.